Sociology of rationality
1 online resource (xix, 248 pages)
Keywords: "This book is a socio-historical analysis of rationalism as a worldview - that guides many of our actions in concrete everyday life - and as a philosophy - that guides our epistemological understanding of the reality around us. It explores the multifaceted manifestations of the idea in the Enlightenment philosophy, modern sociological theorising and in post-structural standpoints. The volume also critiques rationality from feminist, subaltern and post-colonial perspectives. Finally, it delves into the multilayered sociological significances of rationalisation of different domains of life. Transdisciplinary in scope and with essays by foremost scholars in the field, this volume will be a major intervention across the humanities and the social sciences. It will be of interest to students and researchers in sociology, anthropology, history, philosophy, gender studies, political science, cultural anthropology, education, and religious studies"--